9x³-27x²-100x+30 factorise using factor theorem... pls give step by step answer
Answers
Answered by
1
Step-by-step explanation:
The factorisation of 9x^3-27x^2-100x+300=(x-3)(3x+10)(3x-10)9x
3
−27x
2
−100x+300=(x−3)(3x+10)(3x−10) .:
We have,
9x^3-27x^2-100x+3009x
3
−27x
2
−100x+300
To find, the factorisation of 9x^3-27x^2-100x+300=?9x
3
−27x
2
−100x+300=?
∴ 9x^3-27x^2-100x+3009x
3
−27x
2
−100x+300
=9x^2(x-3)-100(x-3)=9x
2
(x−3)−100(x−3)
=(x-3)(9x^2-100)=(x−3)(9x
2
−100)
=(x-3)[(3x)^2-10^2]=(x−3)[(3x)
2
−10
2
]
Using the algebraic identity,
a^{2} -b^{2}=(a+b)(a-b)a
2
−b
2
=(a+b)(a−b)
=(x-3)(3x+10)(3x-10)=(x−3)(3x+10)(3x−10)
∴ The factorisation of 9x^3-27x^2-100x+300=(x-3)(3x+10)(3x-10)9x
3
−27x
2
−100x+300=(x−3)(3x+10)(3x−10)
Hence, the factorisation of 9x^3-27x^2-100x+300=(x-3)(3x+10)(3x-10)9x
3
−27x
2
−100x+300=(x−3)(3x+10)(3x−10) .
Similar questions
Social Sciences,
1 month ago
Science,
3 months ago
Physics,
11 months ago
Science,
11 months ago
History,
11 months ago